Efficacy and MicroRNA-Gut Microbiota Regulatory Mechanisms of Acupuncture for Severe Chronic Constipation: Study Protocol for a Randomized Controlled Trial - Yao, Junpeng; Yan, Xiangyun; Chen, Liping; Li, Yanqiu; Zhang, Leixiao; Chen, Min; Li, Ying (Frontiers in Medicine, 2022)
Background Severe chronic constipation (SCC) is a common functional gastrointestinal (GI) disorder associated with disruptions in GI motility. Abnormalities between gut microbiota and microRNAs (miRNAs) are implicated in the pathogenesis of GI motility in SCC. Acupuncture has been shown to improve constipation-related symptoms and rebalance the gut microbiota. This protocol proposed a plan to explore the hypothesis that the efficacy of acupuncture is associated with the crosstalk between gut microbes and miRNAs in patients with SCC. Methods This trial is designed as a randomized, sham-controlled trial involving 80 patients and 40 healthy volunteers. A total of 80 patients with SCC (≤2 mean spontaneous, complete bowel movements per week [CSBMs]) will be randomly allocated to receive either 16-session acupuncture at true acupoints or non-penetrating sham acupuncture at non-acupoints for 4 weeks. The primary outcome will be the proportion of patients with ≥3 mean weekly CSBMs over weeks 1–4 and 5–8. Secondary efficacy endpoints include bowel movements, stool consistency, degree of straining, and the quality of life. Healthy volunteers will not receive any clinical intervention. Fasting plasma and fecal samples will be analyzed by 16S rRNA third-generation sequencing and miRNA high-throughput sequencing technologies. Finally, a tripartite network analysis will be used to investigate the interactions among clinical efficacy, miRNAs, and intestinal microbiota. Discussion From the perspective of microRNA-gut microbiota regulatory mechanisms, our results will partially illuminate the crucial role of fecal miRNAs and intestinal microbiota to understand how acupuncture exerts its anti-constipation role. Trial registration This trial is registered with ChiCTR2100048831, registered 18 July 2021; ethical approval has been obtained from the Sichuan Regional Ethics Review of Committee on Traditional Chinese Medicine, approval ID: 2021KL-023.